The speed of the body at the moment of transition to a massless state is a new world constant - BG Golovkin (Annals of Mathematics and Physics - Peertechz Publications, 2023)
Based on the kinetic theory of gases, the minimum temperature and critical velocity of a body necessary for its transition to a massless state are estimated. The value of this speed ω = 235696.8871 km⁄s is a new world constant, since it is the same for a body, regardless of its size, mass, density, and chemical composition. For the first time, the masses of X, and Y - bosons, as well as the zeroing temperatures of the mass of elementary particles have been calculated.